Sequential combined treatment with allopurinol and benznidazole in the chronic phase of Trypanosoma cruzi infection: a pilot study - Pérez Mazliah, Damián Eduardo (2012)
Objectives: Even though the use of combined drugs has been proved to be effective in other chronic infections, assessment of combined treatment of antiparasitic drugs in human Chagas' disease has not been performed. Herein, a pilot study was conducted to evaluate the tolerance and side effects of a sequential combined treatment of two antiparasitic drugs, allopurinol and benznidazole, in the chronic phase of Trypanosoma cruzi infection. Patients and methods: Changes in total and T. cruzi-specific T and B cells were monitored during a median follow-up of 36 months. Allopurinol was administered for 3 months (600 mg/day) followed by 30 days of benznidazole (5 mg/kg/day) in 11 T. cruzi-infected subjects. Results: The combined sequential treatment of allopurinol and benznidazole was well tolerated. The levels of T. cruzi-specific antibodies significantly decreased after sequential combined treatment, as determined by conventional serology and by a multiplex assay using recombinant proteins. The frequency of T. cruzi-specific interferon-γ-producing T cells significantly increased after allopurinol treatment and decreased to background levels following benznidazole administration in a substantial proportion of subjects evaluated. The levels of total naive (CD45RA + CCR7 + CD62L+) CD4 + and CD8 + T cells were restored after allopurinol administration and maintained after completion of the combined drug protocol, along with a decrease in T cell activation in total peripheral CD4 + and CD8 + T cells. Conclusions: This pilot study shows that the combination of allopurinol and benznidazole induces significant modifications in T and B cell responses indicative of a reduction in parasite burden, and sustains the feasibility of administration of two antiparasitic drugs in the chronic phase of Chagas' disease.